Multifunctional SiO2@Gd2O3:Yb/Tm Hollow Capsules: Controllable Synthesis and Drug Release Properties - Yang, Guixin; Lv, Ruichan; Gai, Shili; Dai, Yunlu; He, Fei; Yang, Piaoping (Inorganic chemistry, 2014)
A series of hollow and luminescent capsules have been fabricated by covering luminescent Gd2O3:Yb/Tm nanoparticles on the surface of uniform hollow mesoporous silica capsules (HMSCs), which were obtained from an etching process using Fe3O4 as hard templates. X-ray diffraction (XRD), scanning electron microscopy (SEM), transmission electron microscopy (TEM), high-resolution transmission electron microscopy (HRTEM), up-conversion (UC) fluorescence spectra, and N2 adsorption–desorption were used to characterize these samples. It is found that the as-prepared products have mesoporous pores, large specific surface, and high dispersity. In particular, the size, shape, surface area, and interior space of the composites can be finely tuned by adjusting the size and morphology of the magnetic cores. Under 980 nm near-infrared (NIR) laser irradiation, the composites show characteristic blue UC emissions of Tm3+ even after carrying doxorubicin hydrochloride (DOX). The drug-release test reveals that the capsules showed an apparent sustained release character and released in a pH-sensitive manner. Interestingly, the UC luminescence intensity of the drug-carrying system increases with the released DOX, realizing the possibility to track or monitor the released drug by the change of UC fluorescence simultaneously, which should be highly promising in anticancer drug delivery and targeted cancer therapy.